Dental stem cells in intraoral regenerative therapy: a systematic review - Para Kandy, Asmin; Fareed, Nusrath; Basavarajappa, Mohana Kumar; Battur, Hemant; Praveena, Jaseela (Brazilian Dental Science, 2022)
Objective: 1) To critically review the published literature on applications of dental stem cells in the regenerationof intraoral tissues. 2) To provide an evidence-based level on research regarding application of dental stem cellsin intraoral tissues regeneration. Methodology: This systematic review is conducted as per the JBI guidelinesand reported as per the PRISMA. An initial literature search of papers published between 2004 and 2018 yielded421 manuscripts. Nineteen studies satisfied the inclusion / exclusion criteria and were included for qualitativesynthesis. Studies were categorized as animal (11) and human (8) trials. Five independent reviewers criticallyassessed the included studies. Risk of bias was assessed using SYstematic Review Centre for Laboratory animalExperimentation (SYRCLE) bias risk tool, robins-I tool for non-randomised clinical trial and Cochrane Collaboration’sTool for randomised clinical trial. Evidence levels were assessed based on JBI Criteria. Results: Animal trialsmainly focused on periodontal regeneration. A high or unclear Risk of bias was more commonly found amongstanimal studies. Laboratory, clinical and radiographic evaluation were used to assess the outcome. A total ofEight Human studies were conducted on a total samples size of 153 upon a wide age ranging from seven yearsto 60 years. Nearly 70% of the human studies used DPSC for regenerating alveolar bone defects. Conclusion:Appropriate well designed double-blind randomized clinical trials of longer duration are yet to be performed.Evidence for the included studies were 1C and 1D as per the JBI Criteria. Stem cell therapy demonstratedpromising results in Periodontal tissue and alveolar bone regeneration. However, the number of studies to claimsuch a benefit are very limited.KEYWORDSDental stem cell (DSCs); Stem cells from human exfoliated deciduous teeth (SHED); Dental pulp stem cells(DPSC); Intraoral application; Human study; Animal study.